Changes in Invasive Pneumococcal Disease Caused by Streptococcus pneumoniae Serotype 1 Following Introduction of PCV10 and PCV13: Findings from the PSERENADE Project - Bennett, Julia C; Hetrich, Marissa K; Garcia Quesada, Maria; Sinkevitch, Jenna N; Deloria Knoll, Maria; Feikin, Daniel R; Zeger, Scott L; Kagucia, Eunice W; Cohen, Adam L; Ampofo, Krow; Brandileone, Maria-Cristina C; Bruden, Dana; et al. (Microorganisms, 2021)
Streptococcus pneumoniae serotype 1 (ST1) was an important cause of invasive pneumococcal disease (IPD) globally before the introduction of pneumococcal conjugate vaccines (PCVs) containing ST1 antigen. The Pneumococcal Serotype Replacement and Distribution Estimation (PSERENADE) project gathered ST1 IPD surveillance data from sites globally and aimed to estimate PCV10/13 impact on ST1 IPD incidence. We estimated ST1 IPD incidence rate ratios (IRRs) comparing the pre-PCV10/13 period to each post-PCV10/13 year by site using a Bayesian multi-level, mixed-effects Poisson regression and all-site IRRs using a linear mixed-effects regression (N = 45 sites). Following PCV10/13 introduction, the incidence rate (IR) of ST1 IPD declined among all ages. After six years of PCV10/13 use, the all-site IRR was 0.05 (95% credibility interval 0.04-0.06) for all ages, 0.05 (0.04-0.05) for <5 years of age, 0.08 (0.06-0.09) for 5-17 years, 0.06 (0.05-0.08) for 18-49 years, 0.06 (0.05-0.07) for 50-64 years, and 0.05 (0.04-0.06) for ≥65 years. PCV10/13 use in infant immunization programs was followed by a 95% reduction in ST1 IPD in all ages after approximately 6 years. Limited data availability from the highest ST1 disease burden countries using a 3+0 schedule constrains generalizability and data from these settings are needed.
Keywords: invasive pneumococcal disease; serotypes; pneumococcal conjugate vaccines; vaccine impact